Bilateral Pheochromocytoma Presenting with Only Gastrointestinal Complaints: A Case Report - Alireza Norouzi; Abdolreza Fazel; Samaneh Tavassoli; Fatemeh Mohammadzadeh (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: Pheochromocytoma is a rare catecholamine-secreting tumor with gastrointestinal manifestations. Case description: Herein, we report a 50 years old female patient with abdominal pain, altered bowel habit, abdominal mass lesion and laboratory features of pheochromocytoma. The patient was admitted with abdominal pain, back pain, arthralgia, weakness, lethargy, cold sweat and weight loss. She had history of diabetes mellitus, ischemic heart disease and hyperlipidemia. On admission, she was normotensive and had normal physical examination. Upper and lower endoscopies were normal. Transabdominal sonography and CT scan showed large heterogeneous masses with central necrosis and calcification in adrenal regions. In addition, 24-hour urine evaluation showed elevated vanillylmandelic acid, metanephrine and normetanephrine levels. She underwent bilateral adrenalectomy. Pathologic evaluation showed typical characteristics of pheochromocytoma. Conclusions: In any patient with abdominal pain and abdominal mass, low threshold for diagnosis of rare but often lethal pheochromocytoma is suggested. KEYWORDS: pheochromocytoma, constipation, abdominal pain